Developing smart assignment management system using Quick Response (QR) code / Wan Muhammad Khair Mohd Nasir - Mohd Nasir, Wan Muhammad Khair (Faculty of Computer and Mathematical Sciences, 2019)
Assignment management is one of the important things that need to be organized properly because it can affect the student. Nowadays, the use of Quick Response (QR) code has become trending especially when it is used in education. At this moment, student always unaware about their assignment which always leads to tale submitting the assignment since the delivered information sometimes overlooked. Lecturer also having a hard time to check who already submit the assignment because of too many students. Therefore, this project has proposed Smart Class application which has been developed with QR code technology. By using this application, student will get the information via notifications and lecturer just view who did not submit the assignment yet. The developed application has been evaluated using usability, accuracy and performance testing. The result from the testing shows a positive feedback which is around 84.8% are strongly agreed and satisfied with the application. For future work, reminder module is recommended to be integrated with this application because its related to the due dates of the assignment. On the other hand, chat module also can be implemented for student and lecturer as a platform to communicate with each other.